ANALISIS EFEKTIVITAS MEDIA PERCOBAAN LETUSAN GUNUNG MERAPI MENGGUNAKAN STEAM TERHADAP SEMANGAT BELAJAR SAINS SISWA SEKOLAH DASAR - Rohima, Armila Aulia; Utomo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to analyze the effectiveness of the STEAM-based Mount Merapi eruption experiment in increasing the enthusiasm for learning of class VI students at SDN Sawahlega. This approach combines science, technology, engineering, art, and mathematics in interactive learning to increase student engagement. The research used a qualitative descriptive method with 25 students and two teachers as subjects. Data was collected through questionnaires, interviews and observations. The research results show that this experiment is effective in increasing students' enthusiasm for learning. As many as 96% of students stated that learning using media was more fun compared to the lecture method, and 100% of students admitted that experiments helped them understand natural phenomena material. Factors that support the success of this experiment include realistic visualization, a multidisciplinary approach, and a supportive learning environment. Students showed high enthusiasm, teamwork, and great interest in every stage of the experiment, including making miniature mountains and simulating eruptions using simple materials. This experiment not only increases students' enthusiasm for learning, but also strengthens their critical and creative thinking abilities, in line with the demands of 21st century education. This research recommends the application of experiment-based methods in various learning topics to significantly increase student motivation and learning outcome.Keywords: STEAM, Mount Merapi Eruption Experiment, Passion for Learning